(3GdeUHGM aj GdCMGOjK GdUMGMs - (3YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdebOSj GdLeGYjdj GdOeTbj GdMfHdj, CHh eMeO, Jbj GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3Chd GdebQhA efg (B: (3hGHh GdeYGdi CMeO Hf YHO GdZfi Hf MfjaI s
(3BNQgG (B:s
(3aVd YGFTI Ydi GdfSGA caVd GdKQjO Ydi SGFQ GdWYGe bGd CHh ehSi (B: (3gPG MOjK UMjM eJab Ydjg CNQLY GdHNGi (B, (3hCNQLg eSde hGdfSGFi s
(3HgG GKGQ eMhs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B275s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda SfI (B596 (3hYdjgG NW GdeDda HGdUMIs
(3GdfSNI HgG CQVg s
Keywords: (3GdMOjK h GdeUWdMs